Primary spinal extradural Ewing's sarcoma (primitive neuroectodermal tumor): Report of a case and meta-analysis of the reported cases in the literature - Saeedinia, Saeed (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Primary spinal primitive neuroectodermal tumors (PNET) and/or spinal extraskeletal Ewing's sarcoma family tumors (ESET) are rare lesions appearing in the spinal extradural space. One hundred forty-one primary spinal PNETs, including 29 intramedullary lesions, have been reported in the literature. Encountering a case of primary epidural EES/peripheral PNET (pPNET) in sacral level, which is the fifth one occurring at this level in the literature, we have tried to conduct a meta-analysis of the reported cases. CASE DESCRIPTION: A 44-year-old lady with epidural EES/pPNET is reported here. She was once operated for L5/S1 herniated disc, which did not ameliorate her symptoms. The clinical, imaging, surgical, and histopathologic characteristics of our case are presented and wide search of the literature is also done. All the reports were level 3 or less evidences and most of the series had missing parts. 106 cases of primary intraspinal (extradural/extramedullary-intradural) EES/pPNET and 29 cases of primary intramedullary PNET (CNS-PNET) have been reported in the literature. The most common clinical presentation in both entities was muscle weakness proportionate to the tumor location. Distant metastasis occurred in 38 of 99 (38%) cases of primary intraspinal EES/pPNET, while the rate of metastasis was 48% in patients with PNETs occurring in the intramedullary region (P > 0.05). One-year survival rate of the patients who underwent chemo-radiation after total or subtotal resection was better than those who did not receive chemotherapy or radiotherapy, or did not have total or subtotal resection. However, this difference was not repeated in 2-year survival rate in any of the tumor groups. CONCLUSION: It seems that total or subtotal removal of the tumor and adjuvant chemo- and radiation therapy can improve the outcome in these patients.